Design, Synthesis, and Characterization of 0‐D, 1‐D, and 2‐D Zinc–Adeninate Coordination Assemblies. (20th July 2015) - An, Jihyun; Geib, Steven J.; Kim, Myung‐Gil
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10382-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>